Tipping A Broken Scale: The Legality of U.S. Cluster Munitions in Ukraine - Zej Moczydłowski (Washington University Global Studies Law Review, 2024)
Since the 2022 Russian invasion of Ukraine, the United States, NATO countries, EU members, and even distant nations like Japan and New Zealand have aided Ukraine. Support has taken on a multitude of forms, including the treatment of Ukrainian wounded, “a new era of intelligence sharing between Ukraine, the United States, and other allies,” the provision of medical supplies, and the supply of lethal military equipment. Arguably, among the most controversial decisions was the Biden administration’s choice in 2023 to provide cluster munitions. This note examines legal questions arising from that decision. Part I examines cluster munitions, why they are controversial, the ban on cluster munitions, why the US has not joined the ban, and how US policies on cluster munitions have evolved. Part II considers the Russo-Ukraine conflict and the pressures on Ukraine’s allies regarding military aid. Part III discusses arguments supporting and criticizing the US’s decision to offer cluster munitions. Part IV analyzes legal issues surrounding the provision of cluster munitions; these include treaties, case law, the status and intent of the Convention on Cluster Munitions, and the question of how the decision to provide cluster munitions impacts US alliances. Finally, Part V provides a conclusion regarding why the US is both legally and morally justified in providing cluster munitions to Ukraine and why, if the world wants to eliminate the use of Cluster Munitions, it must prevent and punish invasions by aggressor nations.
Keywords: Russia; Russian; Ukraine; War; NATO; EU; Military; Medical assistance; military equipment; lethal; biden administration; cluster munitions; munitions; ban; policies; russo-ukraine; conflict; pressure; military aid; treaty; treaties; convention; convention on cluster munitions; alliances; moral; justify; invasions; aggressor nations